Hypothesis Test of Weak Form of Market Efficiency in Some Selected Stocks - Doley, Satya Ranjan (Indian Journal of Research in Capital Markets, 2022)
The present study attempted to examine the weak-form of market efficiency of a sample of 33 daily stock returns belonging to seven specific sectors in the National Stock Exchange of India for the period from May 18, 2020 – May 12, 2021. The study’s objective was to examine normality and randomness in data series of stock returns for this period. In order to get the desired results, it used means, standard deviation, skewness, kurtosis, Jarque – Bera test, and runs test. The normality test results found that the data of 31 equity stock prices were not normally distributed except for the two stock prices. The outcome of the runs test was that the distribution of daily stock returns of 30 select companies followed a random walk and was the weak-form efficient market.